2016
DOI: 10.1111/ap.12132
|View full text |Cite
|
Sign up to set email alerts
|

Improving Fitness to Drive: The Case for Hazard Perception Training

Abstract: On one hand, individuals who are unfit to drive should not be allowed behind the wheel. On the other hand, being unable to drive can have significant negative consequences for some individuals, including an increased mortality risk. One potential solution to this dilemma is to use training interventions to improve fitness-to-drive. The problem is that, in general, post-licensing driver training and education has a disappointing track record in terms of improving road safety. However, one type of intervention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 87 publications
(111 reference statements)
2
24
0
Order By: Relevance
“…However, as Horswill (2016) claimed, despite the fact that evidence in the literature does not yet completely confirm if simulator trainings (as well as other kinds of training methods) actually reduce on-road crash risk, understanding the behavioral measures that are affected by each kind of training is still important and can allow us to predict crash risk.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…However, as Horswill (2016) claimed, despite the fact that evidence in the literature does not yet completely confirm if simulator trainings (as well as other kinds of training methods) actually reduce on-road crash risk, understanding the behavioral measures that are affected by each kind of training is still important and can allow us to predict crash risk.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Additionally, research has shown hazard perception training to be effective in improving the hazard perception skills of drivers (e.g. Castro et al, 2016;Horswill, 2016;Horswill, Garth, Hill, & Watson, 2017;Vlakveld, 2014;Wetton, Hill, & Horswill, 2013). Therefore the fact that the study indicates that this training is also effective for minority groups such as those with ADHD is an important finding.…”
Section: Discussionmentioning
confidence: 87%
“…Cycling experience was not significantly associated with correctly predicting the driver's behavior, slowing-down, or perceived risk. Previous research showed that hazard detection skills can be improved through experience and training (e.g., Crundall et al, 2012;Horswill, 2016b), but little is known about the relationship between cycling experience and the ability to predict other road users' behaviors. It is possible that cycling experience is not a unique predictor, and that other types of experiences (e.g., driving, walking in traffic) as well as perceptual skills (e.g., speed estimation, interception skill) are predictive of whether one is able to anticipate what a car driver will do next.…”
Section: Tablementioning
confidence: 99%